2011
DOI: 10.1002/app.34965
|View full text |Cite
|
Sign up to set email alerts
|

Fire performance and post‐fire mechanical properties of polymer composites coated with hybrid carbon nanofiber paper

Abstract: In this study, glass fiber reinforced polyester composites were coated with carbon nanofiber/clay/ammonium polyphosphate (CCA) paper and carbon nanofiber/ exfoliated graphite nanoplatelets/ammonium polyphosphate (CXA) paper. The composites were exposed to a heat flux of 35 kW/m 2 during the cone calorimeter testing. The testing results showed a significant reduction in both heat release rates and mass loss rates. The peak heat release rate (PHRR) of CCA and CXA composite samples in the major decomposition peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Also, results showed that the ablative elastomer exhibited a better fire protective performance at low temperatures, whereas the intumescent coating showed a better performance at high temperatures. Zhuge et al [8] developed a carbon nano-fibre based nano-paper and compared its flame retardant efficiency by thermogravimetric analysis and cone calorimeter tests. They found that the nano-paper acted as a thermal barrier, forming a protective char layer.…”
Section: Intumescent Paint and Application Into Hydrogen On-board Stomentioning
confidence: 99%
“…Also, results showed that the ablative elastomer exhibited a better fire protective performance at low temperatures, whereas the intumescent coating showed a better performance at high temperatures. Zhuge et al [8] developed a carbon nano-fibre based nano-paper and compared its flame retardant efficiency by thermogravimetric analysis and cone calorimeter tests. They found that the nano-paper acted as a thermal barrier, forming a protective char layer.…”
Section: Intumescent Paint and Application Into Hydrogen On-board Stomentioning
confidence: 99%
“…The effects of heat flux and heat duration times on the fire structural performance, which is mostly related to the tensile, flexural and compressive properties were reported in various papers. [20][21][22][23][24][25] On the other hand, very few researchers have investigated the post-fire mechanical properties of natural fibre reinforced composites. Rajaei et al investigated the effects of heat-induced damages on impact properties of a flax fibre epoxy composite and compared its performance with one of glass fibre counterpart; 26 however, they did not investigate any thermoplastic composites.…”
Section: Introductionmentioning
confidence: 99%
“…Although the thermal and combustion properties of many thermoplastic matrices are to some extent known, 1,2 the fire performance of thermoplastic composites is still an active area of research. 312 In addition to improving mechanical properties, fibre reinforcement can be used to affect the behaviour of a polymer matrix during a fire. 13…”
Section: Introductionmentioning
confidence: 99%